Day-ahead dispatch approach for cascaded hydropower-photovoltaic complementary system based on two-stage robust optimization. (15th February 2023) - Wang, Zizhao; Wu, Feng; Li, Yang; Li, Jingyan; Liu, Ying; Liu, Wenge
Abstract: Cascade hydropower (CHP) is widely used to increase the integration of photovoltaic (PV) power in recent years. However, the randomness and variability of PV power output might cause power imbalances between generation plan and integrated power of complementary systems. It is crucial to provide robust day-ahead schemes to ensure sufficient adjustment capability of CHPs. In this paper, a day-ahead dispatch model is established for the CHP-PV complementary system to address the PV uncertainties based on the two-stage robust optimization approach. The uncertain PV power output is described by an ambiguity set without accurate probabilistic information. Two different stages in the dispatch model are integrated into a holistic optimization problem. In the first stage, the day-ahead startup/shutdown and operation zone schemes for CHP are determined. In the second stage, the re-dispatch problem is performed to compensate for PV power fluctuations and minimize water consumption. The nested column-and-constraint generation (NC&CG) algorithm is employed as the exact solution methodology. Simulation studies based on a system in southwest China are conducted to validate the effectiveness of the proposed dispatch model and the solution algorithm. The numerical results show that the robust solution can accommodate various scenarios of PV power output and the power imbalance can always be reduced. Highlights: Re-dispatch of cascade hydropower (CHP) is considered in day-ahead dispatch model. Two-stage robust optimization is applied to address PV power uncertainty. Nested column-and-constraint generation (NC&CG) algorithm is employed as methodology. The robust day-ahead solutions can accommodate various scenarios of PV power output.